The dynamics of reciprocal aiming with a steering wheel. - Davis, N; Cui, S; Spence, C (2008)
The study of speed-accuracy trade-offs has a long history in scientists' attempts to understand human movement control. In most such studies of reciprocal aiming, participants have been required to make reaching or pointing movements in space to targets of varying size. We wished to extend this body of work to a situation in which participants had to use a steering wheel in order to move a cursor on a computer monitor. Our results revealed a positive linear relationship between movement times and movement difficulty. We also observed an increased contribution of nonlinear dynamical terms as the movement difficulty increased. These results are consistent with the claim that a linear speed-difficulty relationship is a general feature of human motor control and one which is effector-independent. These results have relevant application to the study of human driving performance.